At their children's expense: How parents' gender stereotypes affect their children's reading outcomes. (April 2019) - Muntoni, Francesca; Retelsdorf, Jan
Abstract: Following expectancy-value theory, we investigated the role parents' reading-related gender stereotypes favoring girls play in explaining students' reading-related competence beliefs, intrinsic task values, and achievement. Drawing on a sample of 1508 students (49% girls, age at T1: 10.89 years) from 60 schools in Germany, we collected data at the beginning of Grade 5 and in the second half of Grade 6 using parent and student questionnaires. Structural equation modeling yielded two main results: First, parents' gender stereotypes favoring girls in reading and their sons' reading-related competence beliefs and intrinsic task values were negatively related. Second, we found indirect effects from parents' gender stereotypes through boys' reading-related intrinsic task values and competence beliefs to boys' reading achievement. Our results provide evidence for the assumption that parents' gender stereotypes are important in the perpetuation of gender differences, as they may affect the development of children's competence beliefs, intrinsic task values, and achievement. Highlights: Role parents' gender stereotypes play for students based on expectancy-value theory. Parents' gender stereotypes negatively affected boys' competence beliefs and values. Boys' competence beliefs and task values in turn affected their achievement. We did not find such significant relations of parents' gender stereotypes for girls. Parents' stereotypes are important for the perpetuation of gender differences.